Assessment of “depression, anxiety and stress” among students of schools at RHTC area catered by private medical college in South India - Zare, V. R.; Ramesh, B.; Kokiwar, Prashant (International Journal Of Community Medicine And Public Health, 2018)
Background: It is important to screen the higher secondary school children for “depression, anxiety, and stress”. This will help in early detection of any such condition. The objective of the study was to assess depression, anxiety and stress among students of schools at RHTC area catered by private medical college in South India. Methods: Institution based cross sectional study was carried out at schools at RHTC area catered by private medical college in South India from April 2017 to December 2017 A total of 400 school children belonging to class 6th to class 10th i.e. 300 from public schools and 100 from private schools were enrolled for the present study. Results: Maximum number of study participants in public school was females (59.33%) and in private school was males (57%). It was found that depression was 13%, anxiety about 63%, stress about 13%. In private school students depression was nearly 6%, anxiety was 60%, stress was 27%. People with depression, anxiety and stress they cope up with those situation by watching TV nearly 94% in private school students and 95% in public school students. None of them share their emotions with friends. Conclusions: Prevalence of “depression, anxiety, and stress” was very high in the study area. Measures like free environment in the schools and recreational activities should be employed in all schools.